Ethics and health care 'underfunding'. Issue 4 (1st August 2001) - Maynard, Alan
Abstract : There are continual "crises" in health care systems worldwide as producer and patient groups unify and decry the "underfunding" of health care. Sometimes this cacophony is the self interest of profit seeking producers and often it is advocacy of unproven therapies. Such pressure is to be expected and needs careful management by explicit rationing criteria which determine who gets access to what health care. Science and rationality, however, are unfortunately, rarely the rules of conduct in the medical market-place.